Preparation method of aluminum-based composite material

By coating nano-oxides on the surface of aluminum or aluminum alloy powder and performing oxidation-reduction reaction, combining micro-scale reinforced aluminum-based composite materials, the problem of insufficient performance of traditional materials under high temperature conditions is solved, and the problem of insufficient performance of traditional materials is achieved. Improved high temperature mechanical properties and thermal stability.

CN116043051BActive Publication Date: 2025-02-07INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211729087.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-02-07
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

Traditional aluminum-based composite materials cannot exert the performance advantages of reinforcement under high temperature conditions, and the preparation process is complex, making it difficult to achieve large-scale industrial applications.

Method used

The nano-enhanced phase is generated in situ with the nano-enhanced phase and the micrometer scale is applied to the surface of aluminum or aluminum alloy powder. Strengthen body bonding to form a multi-scale reinforced structure.

Benefits of technology

The high-temperature mechanical properties of aluminum-based composite materials are improved, the nano-strengthening phase agglomeration phenomenon is avoided, the elastic modulus and thermal stability of the material are enhanced, and the thermal expansion coefficient is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116043051B_ABST
    Figure CN116043051B_ABST
Patent Text Reader

Abstract

The present application provides a method for preparing an aluminum-based composite material, comprising the following steps: step S1: preparing an oxide gel or sol of an M element to obtain a first colloid; step S2: mixing the first colloid with aluminum or aluminum alloy powder, and performing a first drying process and / or a first sintering process to obtain a nano-phase-coated aluminum or aluminum alloy composite powder; step S3: uniformly mixing the nano-phase-coated aluminum or aluminum alloy composite powder obtained in step S2 with a micron reinforcement, and then performing hot pressing sintering, hot isostatic pressing, and the like to obtain a micro-nano-reinforced aluminum-based composite material. According to the method for preparing an aluminum-based composite material of the present application, the added micron-scale reinforcement and the nano-scale reinforcement particles form a multi-scale reinforcement structure, which can greatly improve the elastic modulus, high-temperature strength, and long-term service strength of the aluminum-based composite material, and finally realize the preparation of a high-performance, high-temperature-resistant aluminum-based composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of composite materials, and specifically relates to a method for preparing an aluminum-based composite material. Background Art

[0002] With the rapid development of aerospace, military, transportation, energy and other fields, not only the demand for high-quality, lightweight and high-strength materials is becoming more and more urgent, but also the elastic modulus, thermal expansion coefficient, strength and fatigue resistance of the materials in long-term high-temperature service environment are put forward almost harsh comprehensive requirements, aiming to partially replace titanium alloys and steel in aerospace, military and other fields, thereby reducing the weight of key components and improving the performance of the overall equipment. At present, the commonly used lightweight materials are mainly aluminum and its alloys, but the lower high-temperature strength and elastic modulus and higher thermal expansion coefficient limit their use in many key parts in aerospace, military, transportation and other fields. Aluminum-based composite materials are materials obtained by combining aluminum and its alloys as the matrix with one or more reinforcements. They have a series of advantages such as low density, corrosion resistance, high specific strength and specific stiffness, high elastic modulus and low thermal expansion coefficient. They are widely used in aerospace, military and transportation industries. The micron-scale reinforcements of aluminum-based composite materials are mainly divided into particles (SiC P 、Al 2 O 3P 、TiC P , TiB 2P 、A1N P and B 4 C P etc.), whiskers (Al 18 B 4 O 33W 、SiC W The metal matrix used is usually the traditional 2×××, 4×××, 5××× and 5××× series aluminum alloys.

[0003] However, the above alloying elements (Cu, Mg, Si, etc.) have a high solid solubility in aluminum alloys, and can be strengthened by heat treatment to achieve precipitation phase strengthening and improve the room temperature mechanical properties of aluminum alloys. However, these elements diffuse quickly at higher temperatures, and the precipitation phase coarsening phenomenon is very obvious above 200°C; if the temperature continues to rise, the solid solubility of aluminum to alloying elements will also increase accordingly, resulting in the dissolution of alloying elements in the precipitation phase, and even the disappearance of the precipitation phase, which will greatly reduce the high temperature mechanical properties of aluminum alloys. Usually, the reinforcement has excellent high temperature mechanical properties (such as SiC, TiC, etc.), but with the increase of temperature, the metal matrix softens, the work hardening phenomenon and dislocation pile-up in the metal matrix weaken, and the dynamic recovery and dynamic recrystallization of the matrix material are prone to occur; on the other hand, the interface bonding strength between the reinforcement and the matrix will also be weakened due to the decrease in the strength of the matrix itself, and the ability of the matrix to transfer load to the reinforcement will drop sharply. Therefore, traditional aluminum-based composite materials cannot play the performance advantages of reinforcements under high temperature conditions.

[0004] Although aluminum alloys such as Al-Fe-V-Si and Al-Fe-Cr-Ti have attracted people's attention in recent years, and attempts have been made to make them the matrix of aluminum-based composite materials. However, the preparation process of these high-temperature resistant aluminum alloys is relatively demanding and has not yet been realized in large-scale industrial applications. The addition of reinforcements further increases the difficulty of preparation, resulting in it still being in the laboratory research stage.

[0005] Therefore, how to provide a method for preparing an aluminum-based composite material with a simple process and improved performance of the composite material has become an urgent problem that technicians in this field need to solve. Summary of the invention

[0006] Therefore, the technical problem to be solved by the present application is to provide a method for preparing an aluminum-based composite material, which can simplify the process and improve the performance of the composite material.

[0007] In order to solve the above problems, the present application provides a method for preparing an aluminum-based composite material, comprising the following steps:

[0008] A method for preparing an aluminum-based composite material comprises the following steps:

[0009] Step S1: preparing an oxide gel or sol of the M element to obtain a first colloid;

[0010] Step S2: mixing the first colloid with aluminum or aluminum alloy powder, and performing a first drying process and / or a first sintering process to obtain a nano-phase-coated aluminum or aluminum alloy composite powder;

[0011] Step S3: The nano-phase coated aluminum or aluminum alloy composite powder obtained in step S2 is evenly mixed with the micron reinforcement, and then hot pressing sintering, hot isostatic pressing and other treatments are performed to obtain a micro-nano reinforced aluminum-based composite material.

[0012] Furthermore, the method for preparing the aluminum-based composite material further comprises the following steps:

[0013] Step S21: Repeat step S1 to prepare a sol or gel with the same or different components as the first colloid to obtain a second colloid, mix the second colloid with the nanophase-coated aluminum or aluminum alloy composite powder obtained in step S2, and then perform re-drying and / or re-sintering to obtain multiple nanophase-coated aluminum or aluminum alloy composite powder.

[0014] Furthermore, step S3 also includes the following steps: uniformly mixing the multi-nanophase coated aluminum or aluminum alloy composite powder obtained in step S21 with the micron reinforcement, and then performing hot pressing sintering or hot isostatic pressing to obtain a micro-nano reinforced aluminum-based composite material.

[0015] Furthermore, the method for preparing the aluminum-based composite material further comprises the following steps:

[0016] Before step S3, the nano-phase coated aluminum or aluminum alloy obtained in step S2 or the multi-nano-phase coated aluminum or aluminum alloy composite powder obtained in step S21 is subjected to ball milling treatment;

[0017] Furthermore, in the ball milling treatment, the ball-to-material ratio is 0.5:1 to 30:1; and / or the ball milling speed is 10 to 300 rpm; and / or the ball milling time is 0.5 to 100 h.

[0018] Furthermore, the method for preparing the aluminum-based composite material further comprises the following steps:

[0019] The micro-nano reinforced aluminum-based composite material obtained in step S3 is subjected to cold pressing or cold isostatic pressing to obtain a cold-pressed green body of the aluminum-based composite material; further, the pressure of the cold pressing or cold isostatic pressing is 1.0 to 200 MPa and the time is 0.01 to 24 h;

[0020] Further, the aluminum-based composite material cold-pressed green body is subjected to hot pressing sintering or hot isostatic pressing sintering to obtain the aluminum-based composite material; further, the hot pressing sintering or hot isostatic pressing adopts a temperature of 450-650°C, a pressure of 5.0-300MPa, and a time of 0.5-10h.

[0021] Furthermore, the first colloid and the second colloid are prepared by a sol-gel method;

[0022] The molar concentration of the M element in the first colloid and the second colloid is 0.1 to 4.35 mol / L;

[0023] And / or, a reinforcing element is further added to the first colloid and / or the second colloid, and the reinforcing element is any one or more of B, P and Si;

[0024] And / or, a reinforcing element is further added to the first colloid and / or the second colloid, and the molar concentration of the reinforcing element is 0.05-1.0 mol / L.

[0025] Furthermore, the M element is at least one of the first, second and third transition series metal elements;

[0026] Further, the M element includes any one or more of Ti, Cr, Fe, Mn, Co, V, Zr and W;

[0027] And / or, the oxide of the M element can be reduced by Al and Mg.

[0028] Further, the first drying process includes either or both of natural drying and heat drying;

[0029] And / or, the secondary drying process includes either or both of natural drying or heat drying;

[0030] And / or, the first sintering treatment comprises the following steps: heating a mixture of the first colloid and aluminum or aluminum alloy powder to 80-500° C.;

[0031] And / or, the re-sintering process includes the following steps: heating the mixture of the second colloid and the aluminum or aluminum alloy powder to 80-500°C.

[0032] Further, the micron reinforcement includes any one or more of carbides, nitrides, borides, oxides and carbon materials;

[0033] And / or, the micron reinforcement includes any one or more of a particle reinforcement, a whisker reinforcement and a short fiber reinforcement;

[0034] And / or, in the composite material, the volume fraction of the micron reinforcement is 1.0-25.0%.

[0035] Furthermore, in step S2, mixing the first colloid with aluminum or aluminum alloy powder and performing a first drying comprises the following steps:

[0036] After mixing the first colloid with aluminum or aluminum alloy powder, the mixture is stirred and dried; or, after uniformly mixing the first colloid with aluminum or aluminum alloy powder, the mixture is dried;

[0037] And / or, the particle size of the aluminum or aluminum alloy powder is 0.2 to 100 μm.

[0038] The preparation method of the aluminum-based composite material provided in the present application is different from the conventional method of directly adding nano-reinforced phase (such as nano-TiC) into the metal matrix. P etc.) and micron-scale reinforcements (such as SiC P Compared with the method of preparing the multi-scale reinforced aluminum-based composite material by the sol-gel method, a nano-oxide coating of the element M is coated on the surface of the aluminum or aluminum alloy powder, and an oxidation-reduction reaction occurs between the oxide of the element M and the elements such as Al and Mg in the aluminum or aluminum alloy powder during the hot pressing sintering and hot static pressing process, and a nano-reinforced phase (such as MgAl2O3) is in situ generated at the grain boundary or inside the grain of the aluminum or aluminum alloy. 2 O 4 、Al 2 O 3 ), thereby achieving precise control of the spatial distribution of the nano-reinforced phase in the aluminum matrix, avoiding the agglomeration of the nano-reinforced phase, and the bonding between the nano-reinforced phase and the aluminum matrix is ​​tighter after the in-situ reaction; the added micron-scale reinforcement can significantly increase the elastic modulus of the material and reduce the thermal expansion coefficient; the micron-scale reinforcement and the nano-reinforced phase are coupled and reinforced to achieve the complementary advantages of different materials and give full play to the advantages of the reinforcement such as high strength, high modulus, and low expansion coefficient within the service range from room temperature to high temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 1 vol.% nano-TiO prepared by vacuum hot pressing at 450°C in Example 1 of the present application 2 +1vol.%SiC P / 2009TEM photo of Al composite microstructure.

[0040] Figure 2 0.5 vol.% nano-ZrO prepared by hot isostatic pressing at 650°C in Example 2 of the present application 2 +1vol.%nano-TiO 2 +25vol.%SiC W TEM images of the composite material microstructure.

[0041] Figure 3 The 3 vol.% (TiO 2 +H 3 BO 3 )+5vol.%B 4 C P TEM photo of the microstructure of / 5083Al composite material.

[0042] Figure 4 3 vol.% SiO prepared by 610°C vacuum hot pressing in Example 4 of the present application 2+15vol.%SiC P SEM photograph of the microstructure of / 6061Al composite material. DETAILED DESCRIPTION

[0043] See also Figure 1-4 As shown, a method for preparing an aluminum-based composite material comprises the following steps:

[0044] A method for preparing an aluminum-based composite material comprises the following steps:

[0045] Step S1: preparing an oxide gel or sol of the M element to obtain a first colloid;

[0046] Step S2: mixing the first colloid with aluminum or aluminum alloy powder, and performing a first drying process and / or a first sintering process to obtain a nano-phase-coated aluminum or aluminum alloy composite powder;

[0047] Step S3: The nano-phase coated aluminum or aluminum alloy composite powder obtained in step S2 is mixed evenly with the micron reinforcement, and then hot pressing sintering, hot isostatic pressing and other treatments are performed to obtain a micro-nano reinforced aluminum-based composite material. After sol coating, a network space continuous structure is formed at the aluminum alloy grain boundary. Ball milling can introduce part of the nano-phase into the interior of the grain, and then add micron-scale reinforcement. The aluminum-based composite material of the present application is a heat-resistant aluminum-based composite material.

[0048] In the above step S1, a soluble compound containing the M element is used as a precursor, and a single or doped (such as adding compounds containing elements such as B, Si, P, etc.) oxide sol or gel of the metal M element is prepared by a sol-gel method; the metal M element is one or more of the elements Ti, Cr, Mn, Co, V, Zr and W; the metal M element has the following characteristics: it can be reduced by active elements such as Al in the aluminum alloy in the aluminum matrix.

[0049] In the above step S2, the particle size of the aluminum or aluminum alloy powder used is 0.2 to 100 μm, and the aluminum alloy powder is not limited to conventional aluminum alloy grades. The first colloid obtained in step S1 is mixed evenly with the aluminum or aluminum alloy powder in a certain ratio, and the mixture is dried until there is no liquid or colloid flowing, or it can be dried while stirring until there is no liquid or colloid flowing in the mixture, to obtain a sol- or gel-coated aluminum or aluminum alloy composite powder; the liquid and volatile components in the composite powder are removed by means of the first drying and sintering treatment, so as to increase the bonding strength between the sol or gel coating and the aluminum or aluminum alloy; the aluminum or aluminum alloy powder is mixed evenly with the sol-gel, so as to achieve sol-gel coating on the surface of the aluminum or aluminum alloy powder (or aluminum alloy composite powder), thereby achieving regulation of the spatial distribution of the nanophase.

[0050] The present application also discloses some embodiments, and the method for preparing the aluminum-based composite material further comprises the following steps:

[0051] Step S21: Repeat step S1 to prepare a sol or gel with the same or different components as the first colloid to obtain a second colloid, mix the second colloid with the nanophase-coated aluminum or aluminum alloy composite powder obtained in step S2, and then perform re-drying and / or re-sintering to obtain multiple nanophase-coated aluminum or aluminum alloy composite powder.

[0052] In the above step S21, the second colloid obtained in step S21 and the nano-phase coated aluminum or aluminum alloy composite powder obtained in step S2 are evenly mixed in a certain ratio, and the mixture is dried until there is no liquid or colloid flowing, or it can be dried while stirring until there is no liquid or colloid flowing in the mixture, so as to obtain multiple nano-phase coated aluminum or aluminum alloy composite powder; the liquid and volatile components in the composite powder are removed by means of re-drying and re-sintering treatment, so as to increase the bonding strength between the sol or gel coating and the aluminum or aluminum alloy; the purpose of step S21 is to further increase the types and contents of M elements and reinforcing elements on the basis of step S2, so as to realize the precise regulation of multi-component chemical elements.

[0053] In the multi-scale reinforced aluminum-based composite material prepared in the present application, the oxygen-containing compound of the M element added by the sol-gel method undergoes an in-situ oxidation-reduction reaction with the aluminum or aluminum alloy element, thereby forming a continuous or dispersed Al2O3 layer at the grain boundary and inside the grain of the aluminum or aluminum alloy. 2 O 3 MgAl 2 O 4 Or nano-scale oxygen-containing compounds such as Al-BO, the nano-oxygen-containing compound is the nano-strengthening phase, and its volume fraction is 0.1-10.0%; the reduced M element and Al and other alloy elements can generate Al 3 Ti and other precipitated phases; the volume fraction of the added micron-scale reinforcement body ranges from 1.0 to 25.0%, and the micron-scale reinforcement body and the in-situ generated nano-reinforcement phase form a multi-scale reinforcement structure, which has the advantages of controllable configuration and good thermal stability, etc., and can greatly improve the elastic modulus, high temperature strength and long-term service strength of the aluminum-based composite material, and finally realize the preparation of high-performance, high-temperature resistant aluminum-based composite materials.

[0054] After the oxide sol is coated, it does not react under low temperature conditions, but reacts when the temperature of the subsequent sintering, vacuum hot pressing and hot isostatic pressing treatment is higher.

[0055] In the preparation method of the present application, aluminum or aluminum alloy is used as the matrix, and the reinforcement phase includes micron-scale reinforcement and nano-reinforcement phase. The specific method is: the oxide sol / gel of the M element (one or more of the elements such as Ti, Cr, Fe, Mn, Zr and W) with a low thermal diffusion coefficient in aluminum is evenly mixed with aluminum or aluminum alloy powder, and then mixed with a certain amount of micron-scale reinforcement (SiC P The multi-scale reinforced aluminum matrix composite material is prepared by molding, cold pressing, hot pressing sintering / hot isostatic pressing and other processes.

[0056] The present application also discloses some embodiments, in which step S3 also includes the following steps: the multi-nanophase coated aluminum or aluminum alloy composite powder obtained in step S21 is evenly mixed with the micron reinforcement, and then hot pressing sintering or hot isostatic pressing is performed to obtain a micro-nano reinforced aluminum-based composite material.

[0057] The present application also discloses some embodiments, and the method for preparing aluminum-based composite materials also includes the following steps: before step S4, ball milling the material powder obtained in step S3; then taking out the steel or ceramic balls for ball milling; the purpose of the ball milling is to introduce the oxygen-containing nanophase part added by the sol-gel method into the interior of the aluminum or aluminum alloy grains.

[0058] The present application also discloses some embodiments, in which the ball-to-material ratio in the ball milling process is 0.5:1 to 30:1; the present application also discloses some embodiments, in which the ball milling speed is 10 to 300 rpm; further, the ball milling time is 0.5 to 100 h, which can effectively regulate the distribution of the nanophase inside the aluminum or aluminum alloy grains.

[0059] The present application also discloses some embodiments, and the method for preparing the aluminum-based composite material further comprises the following steps:

[0060] The composite material obtained in step S4 is subjected to cold pressing or cold isostatic pressing to obtain an aluminum-based composite material; the composite material is placed in a mold and subjected to cold pressing or cold isostatic pressing to reduce the gaps between the composite powders.

[0061] The present application also discloses some embodiments, wherein the pressure of cold pressing or cold isostatic pressing is 1.0-200 MPa and the time is 0.01-10 h, which can effectively reduce the porosity of the cold-pressed green body of the aluminum-based composite material;

[0062] The present application also discloses some embodiments, in which the aluminum-based composite material cold-pressed green body is subjected to hot pressing sintering or hot isostatic pressing sintering to obtain the aluminum-based composite material; the present application also discloses some embodiments, in which the temperature used for hot pressing sintering or hot isostatic pressing is 450-650°C, the pressure is 5.0-300MPa, and the time is 0.5-10h, which can achieve the densification of the aluminum-based composite material and obtain a high-performance multi-scale reinforced aluminum-based composite material.

[0063] The present application also discloses some embodiments, wherein in step S1, an oxide gel or sol of the M element is prepared to obtain a first colloid by a sol-gel method;

[0064] The present application also discloses some embodiments, wherein a reinforcing element is added into the first colloid.

[0065] The present application also discloses some embodiments. Before S2, the method for preparing the aluminum-based composite material also includes step S11: preparing an oxide gel or sol of the element M to obtain a second colloid, wherein a reinforcing element is also added to the second colloid; and continuing to add the sol or gel to the aluminum or aluminum alloy composite powder in a certain ratio, wherein the composition of the first colloid and the composition of the second colloid may be different or the same, so as to achieve precise control of the addition of nanophase components in the aluminum alloy.

[0066] The present application also discloses some embodiments, wherein the molar concentration of the M element in the first and second colloids is 0.1 to 4.35 mol / L;

[0067] The present application also discloses some embodiments, when reinforcing elements are added to the first and second colloids, the reinforcing elements are any one or more of B, P and Si, and the reinforcing elements can participate in the in-situ reaction to enrich the types of nano-reinforced phases;

[0068] The present application also discloses some embodiments, in which when a reinforcing element is further added to the first and second colloids, the molar concentration of the reinforcing element added to the first colloid is 0.05-1.0 mol / L.

[0069] The present application also discloses some embodiments, wherein the M element in step S1 is a first, second and third transition metal element, including any one or more of Ti, Cr, Fe, Mn, Co, V, Zr and W;

[0070] The present application also discloses some embodiments, wherein the oxide of the M element can be reduced by Al and Mg;

[0071] The present application also discloses some embodiments, in which the first drying in step S2 includes either or both of natural drying and heat drying; the first drying and second drying are performed by natural or artificial drying to remove liquid components such as water and organic solvents contained in the mixture.

[0072] The present application also discloses some embodiments, wherein the re-drying in step S3 includes any one or both of natural drying and heating drying;

[0073] The present application also discloses some embodiments, wherein the sintering treatment in steps S2 and S3 includes the following steps: heating the nano-reinforced phase to 80-500°C. The sintering treatment refers to heating the dried mixture (80-500°C) to improve the bonding strength between the coating formed by the sol-gel and the aluminum or aluminum alloy powder, and further removing volatile or decomposable products (such as crystal water, OH - NH 4+ wait).

[0074] The present application also discloses some embodiments, wherein the micron reinforcement includes any one or more of carbides, nitrides, borides, oxides, and carbon materials;

[0075] The present application also discloses some embodiments, wherein the micron reinforcement includes any one or more of a particle reinforcement, a whisker reinforcement and a short fiber reinforcement;

[0076] The present application also discloses some embodiments, wherein the micron-scale reinforcement added to the composite material can be selected according to the chemical composition (carbide, oxide, nitride and carbon material, etc.) and shape (particles, whiskers and short fibers, etc.) as needed, and its volume fraction is 1.0 to 25.0%.

[0077] The present application also discloses some embodiments, in which the step S4 of uniformly mixing the material powder and the micron reinforcement also includes the following steps: uniformly mixing the material powder and the micron reinforcement by any one of wet grinding, magnetic stirring, mechanical stirring and ball milling; when ball milling is used for uniform mixing, the ball-to-material ratio is 0.5:1 to 30:1, and the rotation speed is 10 to 300 rpm, so that part of the nano-reinforcement phase can be introduced into the interior of the aluminum or aluminum alloy grains.

[0078] The present application also discloses some embodiments, in which the first colloid is mixed with aluminum or aluminum alloy powder and dried for the first time in step S2, comprising the following steps:

[0079] After mixing the first colloid with aluminum or aluminum alloy powder, the mixture is stirred and dried; or, after uniformly mixing the first colloid with aluminum or aluminum alloy powder, the mixture is dried;

[0080] The present application also discloses some embodiments, in step S2, the nano-reinforced phase is an aluminum or aluminum alloy nano-reinforced phase with the oxide of the M element uniformly coated on the surface;

[0081] The present application also discloses some embodiments, in which in step S2, the particle size of the aluminum or aluminum alloy powder is 0.2 to 100 μm, which is conducive to the regulation of the spatial arrangement of the micron reinforcement and the nano reinforcement phase in the aluminum or aluminum alloy matrix.

[0082] Furthermore, in step S2, the chemical composition of the aluminum alloy is not limited to conventional aluminum alloy grades.

[0083] The aluminum-based composite material of the present application is a multi-scale reinforced aluminum-based composite material.

[0084] The preparation method of the multi-scale reinforced aluminum-based composite material of the present invention firstly adds nano-oxygen compounds of elements such as Ti, Cr, Mn, Co, V, Zr and W to the grain boundaries and grain interiors of the metal matrix, and then utilizes the in-situ reaction occurring during the material preparation or heat treatment process to form the added nano-oxygen compounds, the in-situ reaction products (such as Al 2 O 3 , reaction equation 3TiO 2 +4Al→2Al 2 O 3 +3Ti) and the compounds formed between the reduced products and aluminum alloy elements (such as Al 3 Ti, reaction equation Ti+3Al→Al 3 Ti) as a strengthening phase. On the one hand, the generated Al 2 O 3 MgAl 2 O 4 Oxygen-containing compounds such as Ti, Cr, Mn, Co, V, Zr and W are nanoscale and have excellent high-temperature stability and mechanical properties; on the other hand, elements such as Ti, Cr, Mn, Co, V, Zr and W can diffuse into the interior of aluminum and aluminum alloy grains after being reduced, and form intermetallic compounds with aluminum with good high-temperature stability and mechanical properties, such as Al-Ti, Ti-B, Al-Ti-Cr, Al-Ni-Co and other multi-element compound systems.

[0085] 2. Addition and reaction of nano-strengthening phase (such as Al 2 O 3 ) can not only effectively pin grain boundaries and inhibit the growth of aluminum or aluminum alloy grains, but also effectively pin dislocations, thereby improving the mechanical properties of the aluminum-based composite matrix.

[0086] 3. The added elements such as Ti, Cr, Mn, Co, V, Zr and W have low thermal diffusion coefficients in aluminum and aluminum alloys, which makes it difficult for them to diffuse in aluminum and aluminum alloys (300-400°C), laying a solid foundation for controlling the abnormal growth of precipitation phases in the matrix grains of composite aluminum alloys.

[0087] 4. Multi-scale reinforced aluminum-based composites The in-situ nano-reinforced phase generated in the aluminum alloy matrix can greatly improve the high-temperature performance of the matrix, avoid the dynamic recovery and dynamic recrystallization of the aluminum alloy matrix, increase the softening temperature of the aluminum or aluminum alloy matrix, and enhance the load transfer between the micron-scale reinforcement and the aluminum alloy matrix. Therefore, the mechanical properties advantages of the micron-scale reinforcement can be fully utilized under high-temperature service environment to obtain high-performance metal-based composites.

[0088] 5. The preparation method of the multi-scale reinforced aluminum-based composite material can achieve the precise configuration of nano-reinforcement phase and micron-scale reinforcement by adjusting the type and shape of micron reinforcement (particles, whiskers and short fibers), the composition and particle size of aluminum alloy powder, sol-gel composition, the ratio of sol or gel to aluminum alloy powder, the mixing process parameters of sol or gel and aluminum alloy powder, ball milling process parameters (mechanical alloying), etc.

[0089] The present invention uses a sol-gel method to uniformly mix oxide sol or gel of elements such as Ti, Cr, Co, V, Zr and W (which can be reduced by active alloy elements such as Al and Mg and have a low thermal diffusion coefficient in aluminum) with aluminum or aluminum alloy powder in a certain ratio to achieve uniform coating of nano-reinforced phase on the surface of aluminum or aluminum alloy powder, and then, after drying, sintering or ball milling, mix with a certain amount of micron-scale reinforcement (such as SiC, B 4 C. TiB 2 Etc. particles or whiskers, Al 2 O 3 The invention relates to a method for preparing a multi-scale reinforced aluminum-based composite material by mixing the raw materials and the raw materials evenly, and finally preparing the multi-scale reinforced aluminum-based composite material by processes such as filling a mold, cold pressing, hot pressing sintering / hot isostatic pressing, etc.

[0090] The reinforcing phase or reinforcement in the multi-scale reinforced aluminum-based composites prepared by this method can be divided into two categories: nanoscale and microscale: (1) the nano-oxygen compounds added by the sol-gel method and the Al generated by the oxidation-reduction reaction between the nano-oxygen compounds and the aluminum alloy elements. 2 O 3 MgAl 2 O 4 etc. nano-strengthening phase; (2) added SiC, B 4 C. TiB 2 particles or whiskers, and Al 2 O 3 Micron-scale reinforcements such as short fibers. In addition, the compounds generated between the reduced Ti, Cr, Co, V, Zr, W and Zr and aluminum and its alloying elements (such as Al-Ti, Ti-B and other compounds) also play an important role in improving the mechanical properties of composite materials.

[0091] The multi-scale reinforced aluminum-based composite material prepared in this application can achieve a room temperature modulus of more than 100 GPa and a strength of more than 500 MPa; it can be used for a long time in the range of 300 to 400 ° C, and the tensile strength is higher than 200 MPa. Its advantages are as follows:

[0092] (1) The chemical composition of the nano-reinforced phase is controllable;

[0093] (2) High elastic modulus and low thermal expansion coefficient;

[0094] (3) The spatial distribution of nano-reinforced phase and micro-reinforcement body is controllable;

[0095] (4) The nano-reinforced phase and micro-reinforced body have good high temperature stability;

[0096] (5) The microstructure is stable and controllable under high temperature conditions;

[0097] (6) Little loss of strength during long-term service at high temperatures.

[0098] The preparation method of the multi-scale reinforced aluminum-based composite material of the present application not only solves the problems of low elastic modulus and high thermal expansion coefficient of existing aluminum alloys, but also solves the problems of low high-temperature mechanical properties of existing aluminum-based composite materials, poor high-temperature thermal stability of aluminum alloy matrix precipitation phase, and sharp decline in long-term high-temperature service strength. The present invention adjusts the preparation process parameters such as sol-gel composition, addition amount, and addition order to achieve the spatial distribution of nano-reinforced phases at the grain boundaries and inside the grains of aluminum and its alloy matrix (hereinafter referred to as aluminum alloy matrix), thereby improving the high-temperature mechanical properties of the aluminum matrix; by adjusting the type and addition amount of micron-scale reinforcements, the elastic modulus of aluminum-based composite materials is improved and the thermal expansion coefficient is reduced. Finally, under the coupled reinforcement effect of micron-scale reinforcements and nano-scale reinforcement phases, the mechanical and physical properties of the composite material at room temperature and high temperature are greatly improved.

[0099] Example 1

[0100] The specific steps of this embodiment are as follows:

[0101] (1) Example using TiO 2 The concentration of the sol was 0.1 mol / L. TiO was prepared by the sol-gel method using tetrabutyl titanate as the precursor, anhydrous ethanol as the solvent, acetylacetone as the chelating agent, and nitric acid as the inhibitor. 2 Sol. The volume ratio of tetrabutyl titanate, anhydrous ethanol, deionized water and acetylacetone is 1:9:0.7:0.15. The specific steps are as follows:

[0102] (a) Divide anhydrous ethanol into two portions according to 1 / 3 and 2 / 3 of the total amount;

[0103] (b) mixing a certain amount of deionized water and 1 / 3 of anhydrous ethanol to prepare a solution, and adjusting the pH value of the solution to 3.0 with nitric acid to prepare solution A;

[0104] (c) slowly adding a certain amount of tetrabutyl titanate and acetylacetone to the remaining 2 / 3 of anhydrous ethanol under rapid stirring to prepare solution B;

[0105] (d) Under rapid stirring, solution A was slowly dripped into solution B using a burette to obtain a uniform transparent sol, and then anhydrous ethanol was added to adjust the concentration of the sol to 0.2 mol / L; the obtained TiO 2 The sol is left to age for 24 hours before use;

[0106] (e) Weigh ammonium borate in a ratio of Ti:B of 2:1 and pour it into the TiO 2 In the sol, wait until the ammonium borate is completely dissolved, then add anhydrous ethanol to adjust the TiO 2 The concentration of the sol is 0.1 mol / L, and the concentration of the doped B element is 0.05 mol / L, which is abbreviated as 0.1M-TiO 2 Sol;

[0107] (2) Weigh 10 kg of 2009Al alloy powder with a particle size of about 0.2 to 2.0 μm as raw material, and add 20.12 liters of 0.1M-TiO 2 The sol was added to the 2009Al alloy powder and mixed evenly. The mixture was dried while being stirred until there was no liquid or colloid flowing in the mixture. Then, the mixture was placed in a 40°C explosion-proof drying oven for drying. After vacuum sintering (80°C, 1h), water (including crystal water), alcohol and other volatile or decomposable substances were removed, and the surface-coated nano-TiO 2 2009Al composite powder, referred to as nano-TiO 2 @2009Al composite powder;

[0108] (3) Weigh 121 g of SiC particles (SiC P , particle size is about 5 μm), the nano-TiO 2 @2009Al composite powder and SiC P Put it into the mixing tank, add 5mm diameter steel balls to the mixing tank to improve the uniformity of the mixed powder (ball-to-material ratio is 0.5:1), rotate at 10rpm, mix for 100h, and obtain 1vol.% nano-TiO 2 @2009Al and 1vol.%SiC P Evenly mixed composite powder;

[0109] (4) removing the steel balls from the composite powder obtained in step (3), and then 2 @2009Al+SiC P The composite powder was placed in a mold and cold pressed at room temperature (1 MPa, 24 h);

[0110] (5) placing the mold packaged in step (4) into a vacuum hot pressing furnace and evacuating it (<5 Pa), then heating it to 450° C. at a rate of 10° C. / min, keeping it at that temperature for 0.5 h, and then pressurizing it to 5 MPa, and then keeping it at that temperature and pressure (450° C., 5 MPa) for 4 h, and then cooling it in the furnace;

[0111] (6) After hot pressing and demolding in step (5), 1 vol.% nano-TiO 2 +1vol.%SiC P / 2009Al aluminum matrix composite materials.

[0112] Note: In the multi-scale reinforced aluminum-based composite material obtained by the preparation process of Example 1, TiO 2 In-situ oxidation-reduction reaction occurs between Al and the in-situ generated Al 2 O 3 Mainly distributed at the grain boundaries of aluminum alloy grains (such as Figure 1 As shown); the reduced Ti element forms Al with Al 3 Ti, distributed inside the grains and at the grain boundaries of the aluminum alloy matrix; 1 vol.% nano-TiO 2 +1vol.%SiC P The room temperature tensile strength of the / 2009Al composite material is 470MPa, and the tensile strength at 300℃ is 130MPa.

[0113] Example 1 is 1 vol.% nano-TiO 2 +1vol.%SiC P Preparation of reinforced 2009Al composites (abbreviated as 1 vol.% nano-TiO 2 +1vol.%SiC P / 2009Al)

[0114] Embodiment 2:

[0115] The specific steps of this embodiment are as follows:

[0116] (1) This embodiment uses ZrO 2 The concentration of the sol was 0.5 mol / L, and zirconium oxychloride octahydrate (ZrOCl 2 8H 2 O, chemically pure) as the precursor, and the specific steps are as follows:

[0117] (a) weighing a certain amount of zirconium oxychloride octahydrate and dissolving it in deionized water;

[0118] (b) slowly adding anion exchange resin to the solution of zirconium oxychloride and yttrium oxide under vigorous stirring to adjust the pH value of the solution to 3.0;

[0119] (c) Filter out the anion exchange resin to obtain transparent ZrO 2 The sol is left to stand for use;

[0120] (d) washing the used anion exchange resin with deionized water; soaking the washed anion exchange resin in a 3% NaOH solution for 8 hours; then washing the anion exchange resin with deionized water until the pH value is 7, filtering and drying, and storing for next use.

[0121] (2) This embodiment uses TiO 2 The concentration of the sol was 0.5 mol / L. TiO was prepared by the sol-gel method using tetrabutyl titanate as the precursor, anhydrous ethanol as the solvent, acetylacetone as the chelating agent, and nitric acid as the inhibitor. 2 Sol. The volume ratio of tetrabutyl titanate, anhydrous ethanol, deionized water and acetylacetone is 1:9:0.7:0.15. The specific steps are as follows:

[0122] (a) Divide anhydrous ethanol into two portions according to 1 / 3 and 2 / 3 of the total amount;

[0123] (b) mixing a certain amount of deionized water and 1 / 3 of anhydrous ethanol to prepare a solution, and adjusting the pH value of the solution to 3.0 with nitric acid to prepare solution A;

[0124] (c) slowly adding a certain amount of tetrabutyl titanate and acetylacetone to the remaining 2 / 3 of anhydrous ethanol under rapid stirring to prepare solution B;

[0125] Under rapid stirring, solution A was slowly dripped into solution B using a burette to obtain a uniform transparent sol, and then anhydrous ethanol was added to adjust the concentration of the sol to 0.5 mol / L; the obtained TiO 2 The sol is left to age for 24 hours before use.

[0126] (3) Weigh 5 kg of aluminum powder with a particle size of about 50 to 100 μm as raw material, weigh 1200 ml of ZrO 2 The sol was added to the aluminum powder and mixed evenly, and then placed in a drying oven at 40°C for 24 hours to remove liquid substances such as water and alcohol to obtain a surface-coated nano-ZrO 2 Aluminum composite powder, abbreviated as ZrO 2 @Al composite powder;

[0127] (4) The composite powder obtained in step (2) is placed in a vacuum sintering furnace. When the vacuum reaches 2 Pa, the temperature is raised to 500°C and kept at this temperature for 2 hours. The furnace is then cooled to room temperature to obtain dry ZrO 2 @Al composite powder;

[0128] (5) The ZrO obtained in step (4) 2 @Al composite powder is placed in a mixing tank, according to ZrO 2 Stearic acid was weighed at 1.5% of the weight of the @Al composite aluminum powder, and steel balls were added to the mixing tank to promote uniform mixing (the ball-to-material ratio was 30:1). The sealed mixing tank was installed on the mixer and ball-milled at a speed of 300 rpm for 0.5 h. After removing the steel balls, ball-milled ZrO 2 @Al composite powder;

[0129] (6) Weigh 2680 ml of TiO 2 Sol, the sol and the ZrO 2 The composite powders were mixed evenly and then placed in a drying oven at 40°C for 36 hours to remove liquid substances such as water and alcohol to obtain surface-coated nano-ZrO 2 +nano-TiO 2 The composite powder is referred to as 0.5 vol.% nano-ZrO 2 +1.5vol.%nano-TiO 2 @Al composite powder;

[0130] (7) A certain amount of the composite powder obtained in step (6) is mixed with 2015 g of SiC W (whiskers, diameter 1.5 μm, length 30 μm) were placed in a mixing tank, and mixed for 100 h at a ball-to-material ratio of 1:1, a mixing speed of 10 rpm, and a mixing time of 100 h to obtain SiC W Evenly dispersed 0.5 vol.% nano-ZrO 2 +1.5vol.%nano-TiO 2 +25vol.%SiC W @Al composite powder;

[0131] (8) After taking out the steel balls in the mixing tank in step (6), the composite powder was placed in a cold isostatic pressing bag and cold isostatically pressed at a pressure of 200 MPa for 15 min at room temperature to obtain a cold isostatically pressed green body;

[0132] (9) placing the cold isostatically pressed green body prepared in step (8) into a hot isostatic pressing bag, after vacuum packaging and testing, placing it into a hot isostatic pressing furnace, heating it to 650° C. at a rate of 10° C. / min, keeping it at a pressure of 300 MPa for 0.5 h, and then cooling it in the furnace;

[0133] (10) After removing the hot isostatic pressing jacket, 0.5 vol.% nano-ZrO was obtained. 2 +1vol.%nano-TiO 2 +25vol.%SiC W Reinforced Al-based composites.

[0134] Note: In the multi-scale aluminum-based composite material obtained under the preparation process parameters of Example 2, the in-situ nano-reinforced phase is distributed at the grain boundaries and inside the grains of the aluminum alloy matrix (such as Figure 2 As shown), and reacts with Al element in situ to generate Al 2 O 3 The reduced Ti can diffuse into the interior of the grains to form Al with excellent high temperature mechanical properties. 3 Ti precipitates phase.

[0135] 0.5vol.% nano-ZrO 2 +1vol.%nano-TiO 2 +25vol.%SiC W Preparation of reinforced aluminum matrix composites (abbreviated as 2vol.%nano+15vol.%SiC W / Al)

[0136] Embodiment 3:

[0137] The specific steps of this embodiment are as follows:

[0138] (1) This embodiment uses TiO 2 The concentration of the sol is 1.0 mol / L, and tetrabutylammonium phosphate is doped as a P element source, and the concentration of the P element is 0.3 mol / L;

[0139] (2) weighing 1944 g of 5083Al alloy powder (particle size of about 13.0 μm) according to the ratio, then mixing 1600 ml of the sol prepared in step (1) with the weighed 5083Al alloy powder according to the ratio, and drying while stirring until there is no liquid or colloid flowing in the mixture;

[0140] (3) The powder mixed evenly in step (2) was placed in a drying oven at 40°C and dried for 30 hours to remove liquid substances such as water and alcohol, thereby obtaining a surface evenly coated with nano-TiO 2 +P composite powder;

[0141] (4) Weigh 630 g of B based on a volume fraction of 25% of the micron reinforcement. 4 C P (particle size is about 5 μm), a certain amount of the composite powder obtained in step (3) and B4 C P Put it into the mixing tank, add appropriate amount of steel balls to the mixing tank to improve the uniformity of the mixed powder (ball-to-powder ratio is 3:1), mix at 40 rpm for 6 h, and obtain 3 vol.% (nano-TiO 2 +P)@5083Al+25vol.%B 4 C P Evenly dispersed composite powder;

[0142] (5) placing the composite powder obtained in step (4) into a mold and performing a cold pressing treatment at room temperature (40 MPa, 10 min);

[0143] (6) Place the mold packaged in step (5) into a vacuum hot press furnace and evacuate to 1×10 -1 Pa, then heated to 600℃ at a rate of 10℃ / min, kept at that temperature for 30min, and then pressurized to 35MPa, and then kept at that temperature and pressure (600℃, 40MPa) for 90min, and then cooled in the furnace;

[0144] (7) After hot pressing and demolding in step (6), 3 vol.% (nano-TiO 2 +P)+25vol.%B 4 C P / 5083Al composite material.

[0145] Description: 3 vol.% (nano-TiO 2 +P)+25vol.%B 4 C P In the / 5083Al composite material, TiO 2 In-situ oxidation-reduction reaction occurs between Al and the oxidation products are mainly Al 2 O 3 and MgAl 2 O 4 etc.; the reduced Ti element forms Al with Al 3 Ti is distributed inside the grains and grain boundaries of the aluminum alloy matrix; after hot extrusion deformation at 480℃ and 16:1, the microstructure of the composite material is as follows Figure 3 As shown, the room temperature and 350 °C tensile strengths of the composite material reach 550 MPa and 210 MPa, respectively.

[0146] Example 3 is 3 vol.% nano-TiO 2 +25vol.%B 4 C P Preparation of reinforced 5083Al alloy matrix composites (abbreviated as 3 vol. % TiO 2+25vol.%B 4 C P / 5083Al)

[0147] Embodiment 4:

[0148] The specific steps of this embodiment are as follows:

[0149] (1) This embodiment uses neutral silica sol purchased from the market as raw material. 2 The concentration is 25wt.%, which is equivalent to a SiO2 molar concentration of about 4.35mol / L;

[0150] (2) Weigh 5 kg of 6061Al alloy powder (particle size is about 13.0 μm) according to the ratio, and then mix 520 ml of SiO purchased in step (1) according to the ratio. 2 The sol is mixed with the weighed 6061Al alloy powder, and dried while stirring until there is no liquid or colloid flowing in the mixture;

[0151] (3) The powder mixed evenly in step (2) was placed in a drying oven at 40°C and dried for 30 hours to remove liquid substances such as water and alcohol, thereby obtaining a surface uniformly coated with nano-SiO 2 6061Al composite powder, denoted as nano-SiO 2 @6061Al;

[0152] (4) The nano-SiO obtained in step (3) 2 @6061Al composite powder was placed in an atmosphere protection sintering furnace using Ar / N 2 The mixed gas is a protective gas (Ar and N 2 The ratio of the mixed gas is 1:1), the flow rate of the mixed gas is 1 l / min, the temperature is raised to 80°C at a rate of 5°C / min, and the temperature is kept for 5 hours, and the sintered composite powder is obtained after furnace cooling;

[0153] (5) 1.84 kg of SiC (with a particle size of about 15 μm) was weighed at a ratio of 15% by volume fraction of the micron reinforcement, and a certain amount of the sintered composite powder obtained in step (4) was mixed with SiC P Put it into the mixing tank, add an appropriate amount of steel balls to the mixing tank to improve the uniformity of the mixed powder (the ball-to-powder ratio is 3:1), mix at a speed of 40 rpm for 6 hours, and after sieving out the steel balls, obtain 3 vol.% (nano-SiO 2 )@6061Al+15vol.%SiC P Evenly dispersed composite powder;

[0154] (6) placing the composite powder obtained in step (5) into a mold and performing a cold pressing treatment at room temperature (100 MPa, 0.01 h);

[0155] (7) placing the mold packaged in step (6) into a vacuum hot press furnace, evacuating to 1 Pa, then heating to 450°C at a rate of 10°C / min, keeping warm for 60 min, then heating to 610°C at a rate of 10°C / min, keeping warm for 30 min, and then pressurizing to 35 MPa, then keeping warm and pressurizing (610°C, 40 MPa) for 90 min, and then cooling the furnace;

[0156] (8) After hot pressing and demolding in step (7), 3 vol.% (nano-TiO 2 )+15vol.%SiC P / 6061Al composite material.

[0157] Description: The 3 vol.% (nano-TiO 2 )+15vol.%SiC P In the / 6061Al composite material, SiO 2 In-situ oxidation-reduction reaction occurs between Al and the oxidation products are mainly Al 2 O 3 etc. (such as Figure 4 The room temperature tensile strength and elastic modulus of the composite material reach 450MPa and 130GPa respectively, and the tensile strength at 300℃ reaches 150MPa.

[0158] Example 4 is 3 vol.% nano-SiO 2 +15vol.%SiC P Preparation of reinforced 6061Al alloy matrix composites (abbreviated as 3 vol.% SiO 2 +15vol.%SiC P / 6061Al)

[0159] It is easy for those skilled in the art to understand that, under the premise of no conflict, the above-mentioned advantageous methods can be freely combined and superimposed.

[0160] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements and improvements made within the spirit and principles of the present application shall be included in the protection scope of the present application. The above are only preferred implementations of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present application, and these improvements and variations should also be regarded as the protection scope of the present application.

Claims

1. A method for preparing an aluminum-based composite material, characterized in that: The steps include: Step S1: preparing an oxide sol or gel of the element M to obtain a first colloid; Step S2: mixing the first colloid with aluminum or aluminum alloy powder, and performing a first drying treatment and / or a first sintering treatment to obtain nano-phase-coated aluminum or aluminum alloy composite powder; Step S3: the nano-phase coated aluminum or aluminum alloy composite powder obtained in step S2 is evenly mixed with the micron reinforcement, and then hot pressed or hot isostatic pressed to obtain a micro-nano reinforced aluminum matrix composite material; Wherein, the preparation method of the first colloid is a sol-gel method; The M element is at least one of the first, second and third transition metal elements; the M element includes any one or more of Ti, Cr, Fe, Mn, Co, V, Zr and W; The micron reinforcement includes any one or more of a particle reinforcement, a whisker reinforcement and a short fiber reinforcement.

2. The method for preparing the aluminum-based composite material according to claim 1, characterized in that: The method for preparing the aluminum-based composite material further comprises the following steps: Step S21: Repeat step S1 to prepare a sol or gel with the same or different components as the first colloid to obtain a second colloid, mix the second colloid with the nanophase-coated aluminum or aluminum alloy composite powder obtained in step S2, and then perform re-drying and / or re-sintering to obtain multiple nanophase-coated aluminum or aluminum alloy composite powder.

3. The method for preparing the aluminum-based composite material according to claim 2, characterized in that: The step S3 also includes the following steps: uniformly mixing the multi-nanophase coated aluminum or aluminum alloy composite powder obtained in step S21 with the micron reinforcement, and then performing hot pressing sintering or hot isostatic pressing to obtain a micro-nano reinforced aluminum-based composite material.

4. The method for preparing the aluminum-based composite material according to claim 3, characterized in that: The method for preparing the aluminum-based composite material further comprises the following steps: Before step S3, the nano-phase coated aluminum or aluminum alloy obtained in step S2 or the multi-nano-phase coated aluminum or aluminum alloy composite powder obtained in step S21 is subjected to ball milling treatment; In the ball milling treatment, the ball-to-material ratio is 0.5:1 to 30:1; and / or the ball milling speed is 10 to 300 rpm; and / or the ball milling time is 0.5 to 100 h.

5. The method for preparing the aluminum-based composite material according to claim 1, characterized in that: The method for preparing the aluminum-based composite material further comprises the following steps: The micro-nano enhanced aluminum-based composite material obtained in step S3 is subjected to cold pressing or cold isostatic pressing to obtain a cold-pressed green body of the aluminum-based composite material; the pressure of the cold pressing or the cold isostatic pressing is 1.0 to 200 MPa and the time is 0.01 to 24 h; The aluminum-based composite material cold-pressed green body is subjected to hot pressing sintering or hot isostatic pressing sintering to obtain the aluminum-based composite material; the hot pressing sintering or hot isostatic pressing adopts a temperature of 450-650° C., a pressure of 5.0-300 MPa, and a time of 0.5-10 h.

6. The method for preparing the aluminum-based composite material according to claim 2, characterized in that: The preparation method of the second colloid is a sol-gel method; The molar concentration of the M element in the first colloid and the second colloid is 0.1 to 4.35 mol / L; And / or, a reinforcing element is further added to the first colloid and / or the second colloid, and the reinforcing element is any one or more of B, P and Si; And / or, a reinforcing element is further added to the first colloid and / or the second colloid, and the molar concentration of the reinforcing element is 0.05-1.0 mol / L.

7. The method for preparing the aluminum-based composite material according to claim 1, characterized in that: The oxide of the M element can be reduced by Al and Mg.

8. The method for preparing the aluminum-based composite material according to claim 2, characterized in that: The first drying process includes any one or both of natural drying and heating drying; And / or, the secondary drying process includes any one or both of natural drying and heating drying; And / or, the first sintering treatment comprises the following steps: heating the mixture of the first colloid and aluminum or aluminum alloy powder to 80-500° C.; And / or, the re-sintering process comprises the following steps: heating the mixture of the second colloid and aluminum or aluminum alloy powder to 80-500°C.

9. The method for preparing the aluminum-based composite material according to claim 1, characterized in that: The micron reinforcement includes any one or more of carbides, nitrides, borides, oxides and carbon materials; And / or, in the micro-nano reinforced aluminum-based composite material, the volume fraction of the micron reinforcement is 1.0-25.0%.

10. The method for preparing the aluminum-based composite material according to claim 1, characterized in that: The step S2 of mixing the first colloid with aluminum or aluminum alloy powder and performing a first drying comprises the following steps: After mixing the first colloid with aluminum or aluminum alloy powder, the mixture is stirred and dried at the same time; Alternatively, the first colloid is mixed evenly with aluminum or aluminum alloy powder and then dried; And / or, the particle size of the aluminum or aluminum alloy powder is 0.2 to 100 μm.

Citation Information

Patent Citations

  • Nanometer aluminum oxide reinforced aluminum-based boron carbide, preparation method thereof and neutron absorbing material

    CN114959410A

  • Aerogel-reinforced metal matrix composite material, preparation method and application thereof

    WO2020135582A1